Tropical fruit-derived Lactiplantibacillus as potential probiotic and antifungal agents against Fusarium oxysporum - R. Vasundaradevi; M. Sarvajith; S. Divyashree; N. Deepa; Premila N. Achar; M. Y. Sreenivasa (Scientific Reports)
Abstract Fifty-five lactic acid bacteria (LAB) were isolated from seven selected tropical fruits, with Solanum nigrum exhibiting the highest LAB prevalence and Couroupita guianenis and Musa fruits showing the lowest counts. Two strains isolated from Ficus racemosa demonstrated significant antifungal activity against Fusarium oxysporum. 16S rDNA sequencing identified these strains as Lactiplantibacillus plantarum MYSVCF3 and Lpb. argentoratensis MYSVCF5. The isolates displayed adaptability to a broad range of environmental conditions, including temperatures of 10–45 °C, pH 2–6, and salt up to 7%. The strains tolerated simulated gastrointestinal conditions of acid (pH-2), phenol (0.6%), and bile (0.3%) suggesting potential probiotic attributes. Lpb. argentoratensis MYSVCF5 inhibited F. oxysporum, two ESKAPE group bacteria (P. aeruginosa, S. aureus) plus S. paratyphi and E. coli. The cell-free supernatant (CFS) of Lpb. argentoratensis MYSVCF5 reduced the growth of fungal biomass by 94% and completely inhibited conidial germination, retaining activity even after extended cold storage. LC–MS/MS analysis identified organic acids in the CFS, with citric acid as the most abundant at 34.9 (± 0.3) µg/mL, followed by lactic (8.3 µg/mL) and malic acids (5.2 µg/mL). This study isolated a novel LAB, a potential candidate having probiotics and antifungal properties for application in food and agriculture.